Towards optimising routing overhead in wireless multihop networks. (2015) - Javaid, N.; Bibi, A.; Mohammad, S.N.; Khan, Z.A.; Alrajeh, N.
In this paper, we select three most widely used reactive protocols; adhoc ondemand distance vector (AODV), dynamic source routing (DSR) and dynamic MANET ondemand (DYMO), and model their energy and time consumption costs of expanding ring search (ERS) algorithm in wireless multihop networks (WMhNs). A novel contribution of this work is tuning the route discovery and route maintenance parameters of the chosen protocols to minimise routing overhead. For analytical comparison, we simulate default and enhanced versions of these protocols using NS2. From modelling and analytical comparison, we deduce that adjusting timetolive (TTL) values in search sets of ERS algorithm with respective waiting time is more useful for reducing bandwidth and locating time in chosen protocols. Moreover, for reliable transmission and efficient performance, reactive protocols need immediate detection of link breakage along with quick repairement strategies for reestablishment of routes such as local link repair (LLR) and packet salvaging (PS).